Citizen science initiatives increase pollinator activity in private gardens and green spaces - Persson, Anna S.; Hederström, Veronica; Ljungkvist, Iris; Nilsson, Lovisa; Kendall, Liam (Frontiers in Sustainable Cities, 2023)
Wild insect pollinators are essential to cultivated and natural ecosystems globally. Today, many pollinator species are declining. One reason is a general lack of flowering habitats at landscape scales. However, urban areas, including private gardens, may provide flowers, and constitute beneficial habitats for pollinators. Here, we evaluate the ecological outcomes of a citizen science campaign run by the Swedish Society for Nature Conservation (SSNC) (called “Operation: Save the bees”), encouraging citizens to incorporate interventions beneficial to wild pollinators (garden meadows, flower plantings, and bee hotels) in their gardens. Data on insect observations and flowering plants were collected through online questionnaires at the end of the growing season. In total, we received 3,758 responses for the three interventions. We found that participants were more likely to observe many pollinators (as opposed to few or none) in more species rich garden meadows, and in larger and older plantings. The surrounding environment also affected pollinator abundance: fewer pollinators were observed in plantings in dense urban areas. Direct counts of pollinators during 10-min surveys correlated strongly to the simplistic abundance assessment (none, few, or many insects seen over the summer season). Bee hotel occupancy was positively related to local flower availability and bee hotel age. Smaller nest holes (<10 mm) were more occupied than larger holes (11–15 mm) and hotels in rural gardens and natural/semi-natural sites were more occupied than those in urban gardens. This study demonstrates that flower-rich private gardens provide integral habitat for wild pollinators and that citizen science programs can provide a tool for implementing and evaluating conservation practices. However, longer lasting commitment resulting in older interventions are preferable and should be encouraged in future campaigns.